Case Report: Respiratory lesions successfully treated with intravenous plasminogen, human-tvmh, replacement therapy in four patients with plasminogen deficiency type 1 - Nakar, Charles; McDaniel, Heather; Parker, Joseph M.; Thibaudeau, Karen; Thukral, Neelam; Shapiro, Amy D. (Frontiers in Pediatrics, 2024)
Plasminogen deficiency type 1 (PLGD-1, hypoplasminogenemia) is an ultra-rare, lifelong disease associated with development of fibrinous lesions in multiple organ systems. Depending on lesion location, clinical manifestations of PLGD-1 can result in acute and/or chronic respiratory airway disease which can compromise respiratory function leading to life-threatening events. Early recognition and effective treatment of airway obstruction caused by fibrinous lesions are critical to prevent morbidity due to respiratory compromise. However, physicians may not be familiar with the clinical presentation and management of PLGD-1, causing delays in diagnosis and treatment and potentially contributing to morbidity. Presented here is a case series of one adult and three pediatric patients with severe respiratory complications of PLGD-1 successfully managed by infusions of plasminogen, human-tvmh replacement therapy. Patients' respiratory symptoms were resolved or greatly improved, and treatment was generally well tolerated. In all patients, baseline plasminogen activity was substantially increased with plasminogen replacement therapy administered initially every one to two days followed by extended interval dosing as symptoms were controlled or resolved. All four described cases support the clinical benefit of replacement therapy with plasminogen, human-tvmh in the resolution of life-threatening respiratory complications associated with PLGD-1. Clinical manifestations in addition to respiratory lesions were also improved or resolved with continued treatment.